Mobile, secure, and programmable networking : First International Conference, MSPN 2015, Paris, France, June 15-17, 2015 : selected papers /: First International Conference, MSPN 2015, Paris, France, June 15-17, 2015 : selected papers. (2015) - Unknown
No abstract available